Smart ASN Character Building of Forest Ecosystem Control Functional Officials Through Functional Training Ministry of Environment and Forestry - Siti Maryam (Monas: Jurnal Inovasi Aparatur, 2024)
Forest ecosystem control functional officials (PF PEH) are required to have an ASN character that can adapt to the times and be able to serve the community around the forest well. This study aims to shape the character of Smart ASN PF PEH First Expert in functional training. The study was conducted qualitatively with a literature study by analyzing training subjects that have Smart ASN values. The formation of Smart ASN character in task insight training subjects are the values of nationalism, friendliness, integrity, networking and entrepreneurship. The training course on the implementation of forest ecosystem control contains the values of global insight and IT mastery, whereas forest ecosystem control development training subjects contain the values of IT mastery. Mastery of foreign language values in Smart ASN is shown in the requirements for participants with undergraduate or diploma IV qualifications. Furthermore, these functional officials are also expected to continue improving soft skills to support hard skills in these aspects of Smart ASN.